A liquid cathode/anode based solid-state lithium-sulfur battery. (20th July 2022) - Gao, Yuxuan; Deng, Chao; Fan, Ye; Wang, Shubin; Huang, Shaoming; Lu, Shengguo; Tao, Tao
Highlights: Solid-state Li-S batteries are composed of liquid electrodes and solid-state electrolyte. Such batteries present the liquid-solid electrode/electrolyte interface. The cathode/anode and electrolyte are tightly welded by the liquid-solid interfaces. Symmetric cells show a superior electrochemical performance. The resulting cells show high performance and good structural stability during cycling. Abstract: Solid-state lithium sulfur batteries constantly suffer from a poor interfacial compatibility between solid-state cathode/anode and electrolyte, and low critical current density of Li metal anode (< 3 mA cm −2 ). Here, a concept of a liquid cathode/anode based, room-temperature, solid-state lithium sulfur battery with low impedance electrode/electrolyte interfaces is presented. Due to an extremely stable liquid-solid interface with a high compatibility and unique properties of liquid alloy, the liquid Li-amalgam anode based symmetric cells show a superior electrochemical performance, and no internal short circuit occurs as they run at 55.6 mA cm −2 for 10, 000 cycles. Liquid Li2 S8 polysulfide catholyte can afford a high active material loading (≥135.2 mg mL −1 ) and has a good contact with the solid-sate electrolyte. The cathode/anode and electrolyte are tightly welded together by the liquid-solid interfaces, and the resulting cells show high performance and good structural stability during cycling.